High-resolution fission studies with the planned GBS facility at ELI-NP - D., Choudhury; L., Csige; A.J., Krasznahorkay; D.L., Balabanski; P., Constantin; M., Csatlós; J., Gulyás; A., Oberstedt (Nuclear Science and Technology, 2019)
The emerging photo-fission experimental campaigne with the gamma beam system at ELI-NP is presented along with the physics cases to be addressed, with emphasis on prepared day-one experiments. The design of the state-of-the-art detector arrays, which are under construction for such experiments, is reported. The results of the performance tests of the constructed prototypes are presented. Plans for further extension of the photo-fission experimental programme at ELI-NP are discussed.